Circulating tumor cell profiling for precision oncology. Issue 6 (1st February 2021) - Labib, Mahmoud; Kelley, Shana O.
Abstract : Analysis of circulating tumor cells (CTCs) collected from patient's blood offers a broad range of opportunities in the field of precision oncology. With new advances in profiling technology, it is now possible to demonstrate an association between the molecular profiles of CTCs and tumor response to therapy. In this Review, we discuss mechanisms of tumor resistance to therapy and their link to phenotypic and genotypic properties of CTCs. We summarize key technologies used to isolate and analyze CTCs and discuss recent clinical studies that examined CTCs for genomic and proteomic predictors of responsiveness to therapy. We also point out current limitations that still hamper the implementation of CTCs into clinical practice. We finally reflect on how these shortcomings can be addressed with the likely contribution of multiparametric approaches and advanced data analytics. Abstract : This Review highlights the emerging role of circulating tumor cell (CTC) profiling in precision oncology. We summarize key technologies currently employed for CTC isolation and analysis and discuss recent clinical studies that examined CTCs for genomic and proteomic predictors of therapeutic response. We point out challenges associated with implementation of CTC profiling into clinical practice and reflect on potential solutions.